Scaling climate-smart innovations in Ghana - Ewell, Hanna Louise Deborah; Carbonell Barlis, Angelica; Obeng Adomaa, F; Dalaa, Mustapha Alasan; Tepa Yotto, Ghislain; Zougmore, Robert Bellarmin (2025)
AICCRA Ghana has benefitted more than one million smallholder farmers since 2021 by improving access to climate information services (CIS) and validated climate-smart agriculture (CSA) innovations and technologies. By combining CSA hubs, demonstration plots, digital platforms (Esoko, Farmerline, Syecomp), and community radio, AICCRA Ghana overcame the limitations of single dissemination channels which proved especially effective in expanding women’s access to climate information and technologies. Women and youth were elevated through gender-smart dissemination, technology parks, and entrepreneurship pathways. At the same time, trade-offs—such as input affordability, water use, and digital access gaps—were acknowledged and addressed to ensure sustainable, inclusive resilience outcomes.